ANALISIS ISI KOLOM HIKMAH PADA HARIAN REPUBLIKA - Syahir Syahir (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
General daily Republika characteristics as Islamic-based national newspaper. Wisdom column on the first page of the paper on the progress of orientation marks nerupakan Islam. The research was conducted, the first to know Wisdom column from the aspect of content analysis. The second mission to find the essence of the wisdom contained in the column daily Republika general, be formulated as follows: First how content analysis of newspaper columns on the general wisdom of Republika?. Both how the essence of propaganda is contained in the general field Republika daily lessons?, Perspective is descriptive qualitative approach. Analysis of the data using content analysis aimed to describe and include comparison of the content of media, load ratio between the content of media and social reality. Based on the results of analyzes done on the contents of the